The Behavioral Role of Digital Economy Adaptation in Sustainable Financial Literacy and Financial Inclusion - Liu, Siming; Gao, Leifu; Latif, Khalid; Dar, Ayesha Anees; Zia-UR-Rehman, Muhammad; Baig, Sajjad Ahmad (Frontiers in Psychology, 2021)
The basic aim of this research is to investigate the impact of the behavioural biases on financial inclusion in Pakistan while considering the moderating effect of financial literacy in this relation, in the context of behavioural perspective. This study focused on the significant behavioural phenomenon, including self-control, optimism, herding, and loss aversion with a perspective of the digital economy. To test the proposed hypothesis, the primary data collection method was used. A structured questionnaire was designed to collect data from 102 individual households through the convenience sampling technique. SmartPLS was used to analyze collected data. This study found the negative impact of self-control, optimism, and herding on financial inclusion. In contrast, loss aversion contributes to the uplift of financial inclusion in Pakistan. Similarly, financial literacy proved to have a decreasing effect on financial inclusion because of religious concerns. The moderation effect of financial literacy was also significantly positive except for loss aversion. The behavioural phenomenon proved to have a significant impact on financial inclusion. This research shows that individual households who do not use developed technological services and products from formal financial inclusion can overcome the behavioural biases that hinder them from making informed financial decisions. This research work will significantly help households use financial services to improve their standard of living and overall long-term financial well-being. This research is essential because many households are not using bank services and have low financial knowledge in Pakistan. This research study's key contribution is that it found the relation between behavioural factors and financial inclusion. Financial literacy also has a moderating effect on their relations.